EVALUASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. INCASI RAYA SODETAN DALAM PELESTARIAN LINGKUNGAN HIDUP MASYARAKAT DI NAGARI INDERAPURA KABUPATEN PESISIR SELATAN - Ellysa Wilya Pratama; Syamsir Syamsir (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
The purpose of this research is to find out how Corporate Social Responsibility (CSR) programs are implemented by a company. As it is known that CSR is a programs as a form of responsibility of a company who is in the community environment, both in terms of interests and the operational place of the company itself. PT. Incasi Raya Sodetan is a branch of PT. Incasi Raya Group established since 1997 in Muaro Sakai Inderapura. Indonesian law recognizes that CSR in the law of limited liability company No. 40 In 2007 article 74 to regulate a company’s contribution to employees, commonities, society and the environment. Meanwhile, based on the provisions in Law No. 32 of 2009 on environmental protection and management article 1 paragraph (2) on integrated systematic efforts made to preserve environmental function and prevent pollution or environmental damage which includes planning, utilization, control, maintenance, supervision and law enforcement. Based on this, it is clearly seen about the prohibition on polluting, including hazardous and toxic objects, incorporating waste into the environment and others.